Jejuno-jejunal intussusception: A surgical quandary arising from feeding jejunostomy. (April 2021) - Kohli, Pavneet; Barathi, Deepak; Penumadu, Prasanth
Feeding jejunostomy is a simple and common procedure done for providing enteral nutrition. Though generally safe, complications like dislodgement, clogging and leaking are commonly reported with an incidence as high as 44%. Intussusception is however a much rarer complication which may have catastrophic results and often needs urgent surgical intervention. We describe a case of a patient who underwent robot-assisted minimal invasive oesophagectomy but developed an intestinal obstruction in the follow-up period.